Penerapan Sistem IoT Berbasis Energi Surya untuk Pemberian Pakan Otomatis dan Pemantauan Kualitas Air pada Budidaya Udang Vaname - Razali, Safrizal; Rahman, Aulia; Damora, Adrian (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Vannamei shrimp (Litopenaeus vannamei) merupakan salah satu komoditas utama akuakultur nnasional di Indonesia dengan potensi?ekonomi yang besar. Nonetheless, obstacles like poor water quality and inadequate feed practices prevent sustainable aquaculture. This study aims to design an automatic feeding system for the Internet of Things (IoT) equipped for real-time monitoring of water pH and temperature, powered by solar energy. The system consists of a pH sensor (PH-4502C), a temperature sensor (DS18B20), an ESP32 microcontroller and a Blynk application, which serves as the main interface for the system. The testing was done to prove that this whole system works fine with 2 nos of 100Wp monocrystalline solar panels with 12V 100Ah batter. The system successfully enhances farm operational efficiency, boosts energy sustainability, and offers a novel solution for vannamei shrimp farm management.